REMEMBERING ROMAN SYRIA: VALUING TADMOR‐PALMYRA, FROM 'DISCOVERY' TO DESTRUCTION. (25th June 2019) - BAIRD, J. A.; KAMASH, ZENA
Abstract: The 1753 publication of The Ruins of Palmyra by Robert Wood was key in the formation of archaeological understandings of the site. Examining the original notebooks and drawings of the expedition, which formed the basis for this publication (now held by the Combined Library of the Institute of Classical Studies and the Hellenic and Roman Societies in London), this article examines the relationship between those first documents, the publication, and some of its afterlives. We demonstrate how Wood's treatment of Tadmor‐Palmyra and its inhabitants has shaped memories of the site, prioritizing certain narratives and occluding others, a process that continues today.